2015
DOI: 10.1016/j.biortech.2014.10.117
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of biodiesel-derived glycerol or xylose for increased growth and lipid production by indigenous microalgae

Abstract: The use of industrial wastes rich in mineral nutrients and carbon sources to increase the final microalgal biomass and lipid yield at a low cost is an important strategy to make algal biofuel technology viable. Using strains from the microalgal collection of the Université de Montréal, this report shows for the first time that microalgal strains can be grown on xylose, the major carbon source found in wastewater streams from pulp and paper industries, with an increase in growth rate of 2.8 fold in comparison t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 34 publications
(31 reference statements)
3
37
0
1
Order By: Relevance
“…Similarly, the biodiesel-derived co-production (e.g., glycerol or xylose) could also be recycled for increased growth and lipid production. Leite et al [108] reported that some microalgal strains were capable of mixotrophic and heterotrophic growth on biodiesel-derived glycerol and xylose with the significant increase in growth rate and lipid productivity.…”
Section: Co-production By Biorefinerymentioning
confidence: 99%
“…Similarly, the biodiesel-derived co-production (e.g., glycerol or xylose) could also be recycled for increased growth and lipid production. Leite et al [108] reported that some microalgal strains were capable of mixotrophic and heterotrophic growth on biodiesel-derived glycerol and xylose with the significant increase in growth rate and lipid productivity.…”
Section: Co-production By Biorefinerymentioning
confidence: 99%
“…Polymerase chain reactions (PCRs) were performed in a DNA Engine Peltier thermal cycler PCR (Bio‐Rad) with universal primers 18S rRNA F: 5′‐GTGGTAACGGGTGACGG‐3′ and R: 5′‐GTGCGGCCCAGAACATC‐3′ and Internal transcribed spacer ITS1/ITS4 F: 5′‐TCCGTAGGTGAACCTGCGG‐3ˈand R: 5′‐TCCTCCGCCTTATTGATATCC‐3ˈ for amplification (Leite et al, ). PCR products were purified and successively sequenced at IRIC Genomics Platform (https://genomique.iric.ca) using the Sanger scheme.…”
Section: Methodsmentioning
confidence: 99%
“…For assessment of preeminent, eco‐friendly, and effective approach, it is prerequisite to expand the efficiency and develop economical approaches of biodiesel production from living organisms, let us say the most favorite one are microalgae (Kishore et al, ; Sajjadi, Chen, Raman, & Ibrahim, ). Friendly nature, higher yields per unit area, growing potentially in a variety of water and/or medium and yield more energy per unit weight related to other energy sources are the prevailing advantages of algae for biodiesel production (Abomohra et al, ; Leite, Paranjape, Abdelaziz, & Hallenbeck, ; Zheng et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations